Clonal integration systemically regulates leaf microstructure of Bouteloua dactyloides interconnected ramets to better adapt to different levels of simulated insect herbivory. Issue 2 (13th December 2022) - Chai, Xuxu; Sun, Xiaoling; Cui, Xinyi; Johnson, Paul G; Fu, Zhihui
Abstract: Stolon connection of clonal plants can translocate resources and signalling molecules between interconnected ramets to enhance resistance. Plants are well known to enhance leaf anatomical structure and vein density to respond to insect herbivory. Herbivory signalling molecules are transferred through vascular system to alert distant undamaged leaves, which is called systemic defence induction. Here, we investigated how clonal integration modulates leaf vasculature and anatomical structure of Bouteloua dactyloides ramets to cope with different levels of simulated herbivory. Ramet pairs were subject to six treatments, daughter ramets were exposed to three defoliation levels (0 %, 40 % or 80 % leaf removal) and their stolon connections to mother ramets were either severed or kept intact. Local 40 % defoliation increased vein density and adaxial/abaxial cuticle thickness, decreased leaf width and areolar area of daughter ramets. However, such effects of 80 % defoliation were much smaller. Compared with remote 40 % defoliation, remote 80 % defoliation increased leaf width and areolar area and decreased vein density of interconnected undefoliated mother ramets. Without simulated herbivory, stolon connection negatively affected most leaf microstructural traits of both ramets except from denser veins of mother ramets and more bundle sheath cells of daughter ramets. The negative effect of stolon connection on leaf mechanical structures of daughter ramets was ameliorated in the 40 % defoliation treatment, but not in the 80 % defoliation treatment. Stolon connection increased vein density and decreased areolar area of daughter ramets in the 40 % defoliation treatment. In contrast, stolon connection increased areolar area and decreased bundle sheath cell number of 80 % defoliated daughter ramets. Defoliation signals were transmitted from younger ramets to older ramets to change their leaf biomechanical structure. Clonal integration can adjust leaf microstructure of younger ramets according to the degree of herbivory stress, especially leaf vasculature. Abstract : Plants are well known to enhance leaf microstructure to respond to insect herbivory. Herbivory signalling molecules can be transferred through vascular systems to alert distant undamaged leaves. Here, we found that leaf anatomical structure and vasculature of Bouteloua dactyloides mother ramets were enhanced when interconnected daughter ramets experienced medium defoliation, but not heavy defoliation. Likewise, clonal integration enhanced leaf microstructure of daughter ramets in the medium defoliation treatment and reduced support for daughter ramets when they were grown in the heavy defoliation treatment. Leaf vasculature was more responsive to remote defoliation and clonal integration than leaf anatomical structure.